DOP50 Impact of Inflammatory Bowel Disease associated dysbiosis on bacterial quorum sensing mediated by Acyl-homoserine Lactone in human gut microbiota. (30th January 2023) - Grellier, N; Suzuki, M; Brot, L; Rodrigues, A; Humbert, L; Escoubeyrou, K; Rainteau, D; Grill, J P; Lami, R; Seksik, P
Abstract: Background: Intestinal dysbiosis is a key feature in the pathogenesis of inflammatory bowel diseases (IBD). Bacterial quorum sensing mediated by acyl-homoserine lactones (AHL) might play a role in the dialogue between the gut microbiota and the host. The main objective of our study was to investigate the presence and expression of AHL synthase and receptor genes in the human gut ecosystem during IBD. Methods: To confirm the presence of AHL in the gut, mass spectrometric detection was performed on stool samples from IBD patients and non-IBD subjects. Then, by an in silico approach, we exploited the open access database: Inflammatory Bowel Disease Multi'omics Database, an American cohort with bacterial metagenomes and metatranscriptomes data of stool samples from non-IBD and IBD subjects. To characterise gut dysbiosis, the most discriminating bacterial species between non-IBD and IBD patients were identified by multivariate analysis and allowed us to define two groups (dysbiosis/non-dysbiosis). The search for AHL synthase ( luxI ) and receptor ( luxR ) known homolog genes, was performed using Basic Local Alignment Search Tool (BLAST) from previously assembled gene files (presence/absence) as well as raw data sequencing files (relative abundance and expression). Results: Mass spectrometry confirmed a higher concentration of AHL molecules in healthy subjects than in relapsing IBD. Regarding in silico analysis, 103 subjects were selected including 50 with Crohn's disease (CD), 27 with ulcerative colitis (UC), and 26 non-IBD subjects. No luxI -like synthase genes were retrieved by BLAST searches. However, several homologs of receptor genes were identified: sdiA gene from Escherichia coli (7/103 patients) and luxR -like homologs from Bacteroides fragilis and Bacteroides dorei present in all patients. According to disease, only one luxR -like gene from Bacteroides dorei was under-expressed in IBD patients (p = 0.02) compared to non-IBD, especially in CD (p = 0.02) (Figure 1). In dysbiosis situation, one luxR receptor gene from Bacteroides fragilis appeared to be over-expressed (p = 0.04) compared to non-dysbiotic patients (Figure 2). Conclusion: Through this computational approach, AHL-synthesising bacteria have not been found. However, the expression of quorum sensing receptor genes appears to be modulated by IBD-associated gut dysbiosis. The role of LuxR receptors, especially in Bacteroides species, should be investigated to understand its impact on gut microbiota (Figure 3). Targeting LuxR receptors of bacterial quorum sensing might represent a new approach to modulate the gut microbiota in IBD.